1997
DOI: 10.1046/j.1523-1739.1997.95493.x
|View full text |Cite
|
Sign up to set email alerts
|

Deforestation Predicts the Number of Threatened Birds in Insular Southeast Asia

Abstract: The world’s tropical forests are being cleared rapidly, and ecologists claim this is causing a massive loss of species. This claim has its critics. Can we predict extinctions from the extent of deforestation? We mapped the percentage of deforestation on the islands of the Philippines and Indonesia and counted the number of bird species found only on these islands. We then used the species‐area relationship to calculate the number of species predicted to become globally extinct following deforestation on these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
1
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(180 citation statements)
references
References 47 publications
5
166
1
5
Order By: Relevance
“…Comparably good matches of the numbers of species extinct and predicted to become extinct (plus those presently threatened with extinction) hold for the species-rich insular Southeast Asia (22) and the Atlantic coast forests of Brazil (23).…”
Section: Resultsmentioning
confidence: 89%
“…Comparably good matches of the numbers of species extinct and predicted to become extinct (plus those presently threatened with extinction) hold for the species-rich insular Southeast Asia (22) and the Atlantic coast forests of Brazil (23).…”
Section: Resultsmentioning
confidence: 89%
“…Such a test is impossible on a global scale, but can be attempted for regional-level estimates of extinction. Brooks et al (1997) found a good correspondence between the number of endemic birds predicted to go extinct on individual south-east Asian islands using SAR calculations and information on the extent of deforestation, and a second estimate of extinction risk (from the Red Data Book listings of endangered species on each island). Unfortunately, the logic of this test is somewhat circular because the degree of habitat loss (the variable entered into the SAR calculation) is likely to be a key factor determining whether species on each island are listed as threatened.…”
Section: Species-area Curves and Extinction Predictionsmentioning
confidence: 83%
“…Although quantitative habitat loss rates are lacking for all 220 islands, previous studies using Pimm_s species loss function (11) have shown that habitat loss is a remarkably accurate predictor of past extinction rates (11,12) and current extinction threat (13) on 31 island archipelagoes (12)(13)(14). In fact, whenever accurate habitat loss data are available, they are invariably so highly correlated with observed extinction rates that they confound any attempt to interpret extinctions in the light of species invasions alone.…”
mentioning
confidence: 99%